Chromosomal unbalancements in sperm and oocytes of two Italian cattle breeds as determined by dual color fluorescent in situ hybridization (FISH) - Dino Di Berardino (Italian Journal of Animal Science, 2010)
Aneuploidy is one of the most important causes of embryonic and foetal mortality in mammals. In order to assess the possible risk of chromosomal abnormalities in germ cells of domestic animals we investigated the aneuploidy rates on partially decondensed sperm and in vitro matured oocytes in two cattle breeds, Italian Friesian (I.F.) and Italian Brown (I.B.), by using FISH with chromosome-specific painting probes (chromosomes X-Y for sperm and chromosomes X-5 for oocytes). For each bull, more than 5,000 sperm were analyzed, for a total of 52,586 and 51,342 sperm cells for the two breeds, respectively. Aneuploid and diploid sperm had, respectively, a frequency of 0.110% and 0.050% in the I.F. and 0.078% and 0.062% in the I.B. breeds. Out of 100 in vitro matured oocytes for each breed, on the average, diploidy affected 11.2% and 18.4% in the I.F. and I.B., respectively, whereas disomy for chromosome X-5 had a frequency of 2% in the I.F. and 2.5% in the I.B. breeds. Further studies are needed to expand our knowledge on frequency of aneuploidy in sperm and oocytes of domestic animals, in order to assess their impact on productive and reproductive efficiency, also in relation to climatic changes and environmental hazards.